A new stochastic algorithm to direct orbits of chaotic systems. (4th June 2012) - Cui, Zhihua; Cai, Xingjuan; Zeng, Jianchao
In this paper, a new stochastic optimisation algorithm is introduced to simulate the plant growing process. It employs the photosynthesis operator and phototropism operator to mimic photosynthesis and phototropism phenomena. For the plant growing process, photosynthesis is a basic mechanism to provide the energy from sunshine, while phototropism is an important character to guide the growing direction. In our algorithm, each individual is called a branch, and the sampled points are regarded as the branch growing trajectory. Phototropism operator is designed to introduce the fitness function value, as well as to decide the growing direction. To test the performance, it is used to solve the directing orbits of chaotic systems, simulation results show this new algorithm increases the performance significantly when compared with other four optimisation algorithms.